The Systematic Review of Platelet Rich Plasma Induced Olfactory In Patients With Covid 19 - Nidyasari Citraningrum Satyarini; Salma Rasyidah (Al Makki Health Informatics Journal, 2024)
Background:Olfactory Dysfunction (OD) is a common problem, with a substantial percentage of instances linked to COVID-19. This comprehensive study sought to assess the efficacy of platelet-rich plasma (PRP) in the treatment of COVID-19-related OD, which included anosmia, hyposmia, and parosmia. Aim : This study examined the efficacy of platelet-rich plasma (PRP), an autologous blood product with elevated growth factors, in treating COVID-19-related olfactory dynsfunction. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result:In the PubMed database, the results of our search brought up 9 articles, whereas the results of our search on SCIENCE DIRECT brought up 108 articles. The results of the search conducted for the last year of 2014 yielded a total 17 articles for PubMed and 16 articles for SCIENCE DIRECT. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 2 of which came from SCIENCE DIRECT. We included five research that met the criteria. Conclusion: In summary, injecting PRP directly into the olfactory cleft of individuals with post-COVID COD is a successful and simple treatment. We believe that the therapeutic efficacy of PRP injection may vary depending on the time of OD or with repeated doses. Further randomized controlled studies are needed to confirm these findings and explore the long-term impact of this innovative technique.